2003
DOI: 10.1128/mcb.23.14.4882-4891.2003
|View full text |Cite
|
Sign up to set email alerts
|

Normal Reproductive Function in InhBP/p120-Deficient Mice

Abstract: The inhibins are gonadal transforming growth factor ␤ superfamily protein hormones that suppress pituitary follicle-stimulating hormone (FSH) synthesis. Recently, betaglycan and inhibin binding protein (InhBP/p120, also known as the product of immunoglobulin superfamily gene 1 [IGSF1]) were identified as candidate inhibin coreceptors, shedding light on the molecular basis of how inhibins may affect target cells. Activins, which are structurally related to the inhibins, act within the pituitary to stimulate FSH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
52
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 53 publications
2
52
0
Order By: Relevance
“…Our results corroborate those of an early study showing Igsf1 mRNA expression in adult rat adrenal gland (Bernard & Woodruff 2001). Moreover, both reports suggest that the transcript is derived from an intronic promoter and corresponds to mRNA isoform 4 described in mouse pituitary (Bernard et al 2003). The rat pancreas has not been investigated previously, but IGSF1 mRNA expression has been observed in northern blots of the adult human pancreas (Frattini et al 1998, Mazzarella et al 1998.…”
Section: Figuresupporting
confidence: 81%
“…Our results corroborate those of an early study showing Igsf1 mRNA expression in adult rat adrenal gland (Bernard & Woodruff 2001). Moreover, both reports suggest that the transcript is derived from an intronic promoter and corresponds to mRNA isoform 4 described in mouse pituitary (Bernard et al 2003). The rat pancreas has not been investigated previously, but IGSF1 mRNA expression has been observed in northern blots of the adult human pancreas (Frattini et al 1998, Mazzarella et al 1998.…”
Section: Figuresupporting
confidence: 81%
“…Using the ovine InhBP/p120 probe we confirmed the results obtained by Bernard & Woodruff (2001) since rat InhBP mRNA levels were at least three times higher in metoestrus than pro-oestrus (data not shown, Bernard & Woodruff 2001). However, the same authors have recently shown that mice deficient for both isoforms of InhBP/p120 are fertile and exhibit no obvious alterations in pituitary FSH synthesis or release and normal gonadal physiology and histology (Bernard et al 2003). Thus, these results support our data obtained in the ewe indicating no change in the expression of InhBP/p120 in the pituitary throughout the oestrous cycle, suggesting that InhBP/p120 may not be important for the synthesis and release of FSH.…”
Section: Figuresupporting
confidence: 75%
“…However, 6 patients with macroorchidism had fertility. Whereas the exact mechanism of delayed puberty and macroorchidism is unknown, IGSF1 is expressed in testis [10,12]. Therefore, it is speculated that IGSF1 may play some role in human references…”
Section: Resultsmentioning
confidence: 99%
“…IGSF1 encodes a plasma membrane immunoglobulin super family glycoprotein , containing twelve C2 type immunoglobulin loops, a transmembrane domain, and a short intracellular C terminal domain [11][12][13]. It has been shown that human IGSF1 and mouse Igsf1 are highly expressed in Rathke's pouch and adult pituitary gland and testis [10,12]. In addition, Igsf1 protein is expressed in mouse thyrotropes, somatotropes and lactotropes, but not in gonadotropes [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation